PENGARUH PENAMBAHAN KOTORAN SAPI DAN ENCENG GONDOK (EICCHORNIA CRASSIPES) TERHADAP PRODUKSI BIOGAS DARI LIMBAH JEROAN IKAN - Rosita Dwityaningsih; Nurlinda Ayu Triwuri (INFO-TEKNIK, 2018)
The purposed of this research to study effect of adding cow dung and waterhyacinth to improve biogas production from fish waste. The method of thisresearch used experimental method at batch anaerob reactor and absortion carbonatom used NaOH solution. The result of this research analysis used describtionmethod. The observed of parameter included accumulation of biogas productionand also parameter at slurry incuded temperature and pH. Qualitative parameter istest of flame of biogas. The conclusion value of pH from this research betweencontrol reactor, A1 reactor (fishwaste: cow dung: water hyacinth= 2:9:3), A2reactor (fishwaste: cow dung: water hyacinth= 1:4:2), A3 reactor (fishwaste: cowdung: water hyacinth= 1:3:3) is 5 to 10. Temperature range in 28 oC to 31oC. Theresult indicated the different composition of subtrat slurry from fishwaste, cowdung and water hyacinth in scale 2:9:3 (A1 reactor) produced biogas accumulationand metana the most than the others reactor.